Early Development of Acute Myeloid Leukemia Following Treatment of Osteosarcoma: A Case Report and Review of the Literature - Yu-Mei Shen; Giun-Yi Hung; Hsiu-Ju Yen; Ming-Yun Hsieh; Te-Kuei Hsieh (Elsevier, 2009)
We report a case of treatment-related acute myeloid leukemia (t-AML) in a 16-year-old male following treatment for osteosarcoma (OS). He had been treated with a protocol comprising neoadjuvant chemotherapy, definitive surgery with wide excision and adjuvant chemotherapy for OS. Four months after completion of the treatment, a routine hemogram showed hyperleukocytosis with 90% blasts. Bone marrow aspirate and a chromosomal analysis disclosed acute myeloid leukemia (AML), M5b with 46, XY, t(11;19)(q23;p13.3). The t-AML was characterized by early development (just 4 months after completion of chemotherapy for OS) and generalized leukemia cutis. The patient received an alkylating agent (ifosfamide) and DNA topoisomerase II-targeted drugs (etoposide and doxorubicin). In terms of latency, cytogenetics, and presentation, DNA topoisomerase II-targeted drug-related leukemia seemed likely for this patient. Clinically, his leukemia cutis had developed during a nadir in white blood cell count after the first induction of chemotherapy for AML. The rapid progression and its refractoriness to chemotherapy were poor prognostic signs.